The draft [videorecording (DVD)] - Scott, Campbell (PBS, 2015)
What is the price of citizenship in time of war? What are the limits to government authority over the liberty of a free people? Does the military draft have a place in American democracy? Since the birth of the United States, these questions have driven a defining national debate. This documentary, first aired on PBS, unpacks the history and the arguments that have shaped military conscription in the United States.--Adapted from container.